Long Non-coding RNA DLEU2L Targets miR-210-3p to Suppress Gemcitabine Resistance in Pancreatic Cancer Cells via BRCA2 Regulation - Xu, Fei; Wu, Heshui; Xiong, Jiongxin; Peng, Tao (Frontiers in Molecular Biosciences, 2021)
Gemcitabine (GEM) resistance remains a challenging clinical issue to overcome in chemotherapy against pancreatic cancer. We previously demonstrated that miR-210 derived from pancreatic cancer stem cells enhanced the GEM-resistant properties of pancreatic cancer cells, thus identifying miR-210 as an oncogenic miRNA. Herein, we report the existence of an upstream effector that acts as a competing endogenous RNA (ceRNA) to miR-210. Bioinformatic screening was performed to identify lncRNAs with a binding relationship to miR-210. Overexpression and interference vectors were constructed to demonstrate the effect of ceRNA activity in pancreatic cell behavior, both in vitro and in vivo. DLEU2L (deleted in lymphocytic leukemia 2-like), which is expressed at low levels in pancreatic cancer tissues, was shown to exhibit a binding relationship with miR-210-3p. Overexpression of DLEU2L and silencing of miR-210-3p suppressed the proliferation, migration, and invasion of pancreatic cancer cells while promoting apoptosis. These effects occurred via the inhibition of the Warburg effect (aerobic glycolysis) and AKT/mTOR signaling. In addition, we showed that BRCA2 is a target gene of miR-210-3p, and the downregulation of miR-210-3p by DLEU2L effectively induced an upregulation of BRCA2 via the ceRNA mechanism. In vivo, DLEU2L overexpression and miR-210-3p interference suppressed pancreatic tumor progression, consistent with the results of in vitro studies. The findings of our study establish DLEU2L as a ceRNA to miR-210-3p and reveal the critical role of the DLEU2L/miR-210-3p crosstalk in targeting GEM resistance.